Prognostic impact of implantable cardioverter defibrillators and associated adverse events in patients with continuous flow left ventricular assist devices - Pausch, Jonas; Mersmann, Julian; Bhadra, Oliver D.; Barten, Markus J.; Tönnis, Tobias; Yildirim, Yalin; Pecha, Simon; Reichenspurner, Hermann; Bernhardt, Alexander M. (Frontiers in Cardiovascular Medicine, 2023)
Objectives Implantation of implantable cardioverter defibrillators (ICD) reduces the risk of all-cause mortality in symptomatic heart failure (HF) patients with severe left ventricular (LV) dysfunction. Nevertheless, the prognostic impact of ICD therapy in continuous flow left ventricular assist device (LVAD) recipients remains controversial. Methods 162 consecutive HF patients, who underwent LVAD implantation at our institution between 2010 and 2019, were categorized according to the presence (n = 94, ICD-group) or absence (n = 68, Control-group) of ICDs. Apart from clinical baseline and follow-up parameters, adverse events (AEs) related to ICD therapy and overall survival rates were retrospectively analyzed. Results Out of 162 consecutive LVAD recipients 79 patients (48.8%) were preoperatively categorized as Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) profile ≤2. The prevalence of severe HF symptoms and preoperative use of short-term circulatory support devices (54.4% vs. 13.8%, p < 0.001) was higher within the Control-group, although baseline severity of LV and RV dysfunction was similar. Apart from an increased prevalence of perioperative right heart failure (RHF) within the Control-group (45.6% vs. 17.0%; p < 0.001), procedural characteristics and perioperative outcome were similar. Overall-survival during a median follow-up of 14 (3.0–36.5) months was similar within both groups (p = 0.46). During the first 2 years after LVAD implantation 53 ICD-related AEs occurred within the ICD-group. Thereof, lead-dysfunction occurred in 19 patients and unplanned ICD-reintervention in 11 patients. Furthermore, in 18 patients appropriate shocks without loss of consciousness occurred, whereas inappropriate shocks occurred in 5 patients. Conclusion ICD therapy in LVAD recipients was not associated with a survival benefit or reduced morbidity after LVAD implantation. Conservative ICD-programming seems to be justified to avoid ICD-related complications and „awake shocks” after LVAD implantation.